Major Stress-Strain State of Double Support Multilayer Beams Under Concentrated Load. Part 1. Model Construction - Kovalchuk, S.B.; Gorik, A.V. (Проблеми машинобудування, 2018)
The purpose of this paper is to design an analytical model for bending double support multilayer beams under concentrated load based on the previously obtained solution of the elasticity theory for a multi-layer cantilever. Метою цієї роботи є побудова аналітичної моделі вигину двохопорних багатошарових балок під дією зосередженого навантаження на основі отриманого раніше розв’язку теорії пружності для багатошарової консолі. Цель данной работы – построение аналитической модели изгиба двухопорных многослойных балок под действием сосредоточенной нагрузки на основе полученного ранее решения теории упругости для многослойной консоли.